2004
DOI: 10.1086/421404
|View full text |Cite
|
Sign up to set email alerts
|

Directly Observed Therapy for the Management of HIV-Infected Patients in a Methadone Program

Abstract: The objective of this prospective, observational clinical study was to evaluate the safety and efficacy of once-daily and twice-daily directly observed therapy (DOT) in human immunodeficiency virus (HIV)-infected patients undergoing methadone treatment. Methadone and highly active antiretroviral therapy (HAART) were dispensed daily as DOT, with patients in the twice-daily HAART group self-administering the second dose. Clinical and laboratory end points were monitored, along with the impact of ongoing cocaine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 25 publications
3
68
0
1
Order By: Relevance
“…29 It has been shown that once HAART is initiated, the response is similar among injecting drug users and noninjecting drug users. 2,30 However, most authors have described worse virological responses 31 and, in general, a higher risk of progression to AIDS and death among IDUs. 13,17,31 We have also observed that IDUs show poorer viral suppression responses than other transmission categories after adjustment for viral load and level of CD4 at the onset of treatment, previous AIDS diagnosis, and previous treatment with antiretrovirals.…”
Section: Rodríguez-arenas Et Al 718mentioning
confidence: 99%
“…29 It has been shown that once HAART is initiated, the response is similar among injecting drug users and noninjecting drug users. 2,30 However, most authors have described worse virological responses 31 and, in general, a higher risk of progression to AIDS and death among IDUs. 13,17,31 We have also observed that IDUs show poorer viral suppression responses than other transmission categories after adjustment for viral load and level of CD4 at the onset of treatment, previous AIDS diagnosis, and previous treatment with antiretrovirals.…”
Section: Rodríguez-arenas Et Al 718mentioning
confidence: 99%
“…This was likely the result of participants being expelled from the methadone program if they were found to be using illicit drugs (Lucas et al 2007). Although one might expect ongoing heroin and cocaine use to be important predisposing factors, these have not been strongly associated with outcomes (Conway et al 2004;. On the other hand, the enabling factor of participation in a methadone program has improved DAART utilization in other studies (Arnsten et al 2007;Lucas et al 2004Lucas et al , 2006b).…”
Section: Introductionmentioning
confidence: 97%
“…One strategy to improve adherence in this vulnerable population, adapted from directly observed therapy for tuberculosis control, is directly administered antiretroviral therapy (DAART). Recent data from feasibility pilot studies (Altice et al 2003;Behforouz et al 2004;Conway et al 2004;Greenberg et al 1999;Macalino et al 2004;Mitchell et al 2007;Mitty et al 2005;Tinoco et al 2004;Tyndall et al 2007), case-control evaluations (Lucas et al 2006b), and prospective randomized controlled trials ; Arnsten et al 2007;Macalino et al 2007) support DAART implementation among patients with poor adherence. One randomized controlled trial among inner-city patients did not support DAART (Wohl et al 2006); however, the population studied did not have a previous history of problematic adherence .…”
Section: Introductionmentioning
confidence: 99%
“…The study results indicated that 34 (65%) of participants achieved HIV viral suppression at the two year follow-up. The study showed that DOT can be successful for even the most difficult to treat -a category that people who use injection drugs fit into (Conway et al, 2004).…”
Section: Hiv Treatment -Highly Active Antiretroviral Therapy (Haart)mentioning
confidence: 99%
“…Of the 60 patients, only 4 (6.7%) abstained from illicit drug use for the duration of the study and the study adherence rate was 84.5%. Conway, Prasad, Reynolds, Farley, Jones, et al (2004) conducted a study that evaluated the use of directly observed therapy (DOT) for the management of HAART for patients in a methadone program. The study enrolled 54 patients, of which, 48 (89%) continued to actively use injection drugs throughout the study period.…”
Section: Hiv Treatment -Highly Active Antiretroviral Therapy (Haart)mentioning
confidence: 99%